IDENTIFICATION AND ANALYSIS OF GENETIC EPILEPSY AND EPILEPTIC ENCEPHALOPATHIES IN THE OUTPATIENT PRACTICE OF EPILEPSY SPECIALISTS - Rakhmanina, Olga; Volkov, Iosif; Shestakova, Olga; Tomenko, Tatyana; Volkova, Oksana; Levitina, Elena; Belyaev, Ðžleg (Malang Neurology Journal, 2020)
Background: Given the significant share of gene mutations in the etiology of epilepsy, it is important for the practitioners to evaluate progress in this area.Objective: To describe the spectrum of being detected gene mutations in patients with epilepsy or epileptic encephalopathy in clinical practice of neurologists specializing in epilepsy with an analysis of diagnosed epileptic syndromes, the characteristics of seizures, the timing of a genetic diagnosis, options and treatment efficacy.Methods: The study included 100 patients (40 boys, 60 girls) with epilepsy/epileptic encephalopathy and a gene mutation identified. The average age was 6.9Â±5.1 years. Through remote access, epilepsy specialists filled out a specially designed unified table containing information from outpatient case history.Results: In the outpatient practice of epilepsy specialists, there are patients with a wide range of gene mutations, the leading of which is a mutation in the SCN1A gene (15%). Nowadays, the main method (85%) of detection remains the next generation sequencing in the â€œHereditary Epilepsyâ€ panel. Years pass from the onset of the disease to the genetic diagnosis (Me - 3 years). In most cases, patients with severe (52% have epileptic encephalopathy, 88% have developmental disorders) and pharmacoresistant (mean amount of anti-epileptic drugs - 3,8Â±2,2, multitherapy -70%) syndromes have undergone genetic testing. In the treatment of these patients epileptologists are increasingly (52%) use alternative methods: steroids, ketogenic diet and others. The absence of seizures was observed only in 46% of patients.Conclusion: Thus, in the outpatient practice of epileptologists of Russia, patients with a wide range of gene mutations are found. As a rule, these are patients with severe, therapy-resistant epileptic syndromes.